The Mediation Role of Internship Satisfaction on Career Intention as Internship Program Results in Indonesia - Athiyyah Adhikaputri; Fanny Martdianty (Universitas Negeri Malang, 2022)
This study focuses on the role of internship satisfaction as a mediation variable in the relationship between its determinants on Indonesian students’ future career intentions. The factors of internship satisfaction used in this research include individual factors, university support, organizational environment, and job characteristics. Through an online survey, 412 responses related to student internship experience from 159 universities across Indonesia were gathered and analyzed using Structural Equation Methods. The data processing results show that individual and university factors do not significantly affect internship satisfaction and career intention. However, organizational environment and job characteristics positively influence career intention by mediating internship satisfaction. This paper indicates the interesting results, comparing previous studies held in varied contexts. Theoretical and managerial implication for internship practices in Indonesia is also discussed. However, there are some limitations in the contextual conduct of this research, and future research possibilities are also discussed at the end of this paper. Keywords: Internship satisfaction, Career intention, Organizational environment, Job characteristic